Analisis Best Practice pada Program Layanan “Siapel Tegas” di Dinas Kependudukan dan Pencatatan Sipil Kota Malang - Prakosa, Sakti Sigap; Pertiwi, Vidya Imanuari (IAI Nasional Laa Roiba Bogor, 2024)
Administrative services in Indonesia still face various issues such as the presence of intermediaries, slow e-KTP printing, and suboptimal data consolidation. The